Elsberg Syndrome, Lumbosacral Radiculopathy, and Myelitis Due to Herpes Zoster in a Patient With Smoldering Myeloma - Rohan Desai MS4; Cynthia T. Welsh MD; Samuel O. Schumann MD, MSCR (SAGE Publishing, 2022)
Herpes zoster (HZ) is a common illness caused by the reactivation of latent varicella zoster virus (VZV) due to waning immunity, often secondary to old age or an underlying immunocompromised state. Its complications can manifest in variety of ways, including persistent neuralgias, vasculopathies, and stroke. Here, we describe a case of a 45-year-old man with a history of cryptogenic stroke and smoldering myeloma who was admitted with sacral HZ complicated by right lumbosacral radiculopathy and myelitis, otherwise known as Elsberg syndrome (ES). He was found to have an enhancing lesion in the peripheral conus medullaris on magnetic resonance imaging (MRI) with nonspecific inflammation and necrosis on biopsy pathology and cerebrospinal fluid (CSF) polymerase chain reaction (PCR) positive for VZV. The patient was initially treated with intravenous acyclovir and dexamethasone and discharged with a steroid taper and indefinite valacyclovir therapy. Twelve months postdischarge, the patient's right lumbosacral radiculopathy and myelitis had almost completely resolved; however, he continued to require bladder self-catheterization. We believe that the patient's underlying smoldering myeloma lead to an immunocompromised state, allowing for reactivation of latent VZV, resulting in both the patient's cryptogenic stroke years earlier and recent ES.